Structural Factors and Policy Change as Related to the Quality of Early Childhood Education and Care for 3–4 Year Olds in the UK - Melhuish, Edward; Gardiner, Julian (Frontiers in Education, 2019)
In many developed countries it is now the norm for preschool children to spend time outside the home in early childhood education and care (ECEC). Research indicates that attending ECEC can promote longer-term positive life outcomes, which is more likely when the ECEC is of higher quality. In a UK Study of 600 ECEC group settings for 3-4 year olds, staff qualifications were predictive of quality at private (for profit) settings. For voluntary (not for profit) settings, which were more homogenous in staff qualifications, having a staff training plan and a better staff to child ratio were found to be significant predictors of quality. However, state funded nursery classes / schools, which tend to have less favourable staff to child ratios than private and voluntary settings, also tended to have higher process quality ratings, where the presence of more highly qualified staff apparently allowed quality to be maintained with a larger number of children per staff member. A comparison of equivalent quality data from separate UK studies, conducted before and after a period of substantial policy change in relation to ECEC quality, indicated that policy change may have powerful effects in improving ECEC quality with implications for long-term child, and potentially adult, well-being.